A maritime safety on-board decision support system to enhance emergency evacuation on ferryboats. Issue 4 (19th May 2019) - Sarvari, Peiman Alipour; Cevikcan, Emre; Celik, Metin; Ustundag, Alp; Ervural, Bilal
ABSTRACT: Planning emergency evacuation operations in a proactive manner in public marine transportation systems is a critical success factor for passenger and crew safety. Despite the fact that there is a growing attention on safety issues for marine transportation systems, providing a real-time decision support for evacuation planning under different emergency conditions has not yet been addressed. In this context, this paper contributes to the related literature by providing a comprehensive methodology including simulation and statistical analysis along with a three-module decision support system (DSS) for ferryboat emergency evacuation. Emergency evacuation and fire environment are simulated via Maritime EXODUS V5.1 and SMARTFIRE V4.3, respectively. The methodology is applied to a real-life Ro-Ro ferry, and the results not only revealed significant factors on emergency evacuation performance, but also demonstrated the validity of the developed decision support system.